Peran Hukum Dalam Legalitas Dan Keabsahan Badan Usaha Dalam Dunia Bisnis - Masitho Marwa; Veni Kisnawati; Haiyul Qoiyum; Agus Wahyudi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
Corporations always interact with external entities to maintain the integrity of a law-abiding company (“in good faith”), highlighting the importance of corporate legality in commercial endeavors. One of the most critical aspects is the legality of a company or business organization, as it embodies the fundamental principle that enables a company to be recognized by society and legitimized. A company must be considered valid in accordance with relevant laws and regulations, under which it is protected or safeguarded by various legal documents until they acquire legal force. Forms of Corporate Legitimacy: Corporate nomenclature, brand identity, and commercial operating licenses are some forms of identification that confer legitimacy upon a company. Corporate legitimacy also serves as legal protection, a promotional tool, evidence of legal compliance, facilitates project acquisition, and accelerates business growth. A company established without legal formalization can result in significant losses for other entities consistently involved in its business activities.